WITH THE HELP OF CLINICAL AND LABORATORY RESEARCH METHODS, TO STUDY THE MORPHOLOGICAL STATE OF THE DENTAL SYSTEM IN CHILDREN - B.N., Nekov (Research Journal of Trauma and Disability Studies, 2023)
A polyetiological anomaly is the retention of teeth. General and local factors have a great influence, among them: early removal of baby teeth, incorrect tactics of orthodontic treatment, violation of the order of eruption of permanent teeth, lack of space in the dentition, anomaly of the position of the rudiment of a permanent tooth, underdevelopment of the jaw, shortening of the dentition, displacement of adjacent teeth, narrowing of the jaw base, endocrine and metabolic disorders in the body , etc .